Optimalisasi Decision Quality: Efek Langsung dan Tidak Langsung dari Workload, Pelatihan, dan Resiliensi Psikologis melalui Burnout Reduction - Cahyani, Diah; Al Hakim, Yusuf Rahman; Irfan, Mochamad (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2025)
This study investigated the direct and indirect effects of workload, psychological resilience, and decision-making training on burnout reduction and decision quality among worker-students in Mojokerto Regency and City. Adopting an explanatory quantitative approach within a positivist paradigm, the analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) on a sample of 97 respondents selected through purposive sampling. The results indicated that decision-making training significantly influenced both burnout reduction and decision quality, both directly and indirectly. In contrast, workload and psychological resilience did not show significant effects on either burnout reduction or decision quality. These findings highlight the critical role of cognitive training as a strategic intervention for enhancing decision-making in high-work-intensity environments. The study is limited by its specific contextual focus and the exclusion of broader external variables. The practical implications suggest a need for training-based interventions to manage occupational stress.